Spatial and Temporal Variation of Nitrate-N in Groundwater at IARI Farm - Dash, Ch. J.; Sarangi, A; Singh, D K (Journal of Agricultural Engineering, 2012)
Continuous loading of agrochemicals, a common phenomenon in intensive agriculture, results in groundwater pollution as these chemicals move with irrigation water to the aquifer. Ground water monitoring undertaken for a period from November 2007 to May 2009 at the farm of Indian Agricultural Research Institute (IARI), New Delhi revealed that nitrate-N concentration ranged from a minimum of 6.9 mg.l-1 to a maximum of 26.2 mg.l-1 with a mean of 14.0 mg.l-1. The spatio-temporal variability map of nitrate load generated through geostatistical wizard of ArcGIS revealed that N concentration exceeded 15 mg.l-1 in the western part of the farm. The area under this high nitrate-N load varied from a minimum of 5% in one season to a maximum of 28% of total farm area in the other season